An evaluation of knee overuse injuries and sleep disturbance among men and women fencers - Ma, T.; Zhang, H.; Ghigiarelli, J. (Research Square, 2020)
Fencing is an Olympic sport, it has many associations and competitions around the world. Modern fencing originated in ancient European fencing duels, which was popular among the nobility and became a way of resolving conflicts. Not only did fencing rise in Europe, but also it was popular in ancient Egypt, China, Arabia and other countries. China first combined the theory of fencing with the theory of politics. According to ancient Chinese records, in the 4th century BC, the Chinese philosopher Zhou Zhuang taught the King of Zhao the philosophy of fencing. Zhou Zhuang declared that if the King used the blade, he should observe the political environment of the whole county, following the wills of the people and the laws of nature. Then, he could make the whole county obey him. France is the cradle of modern fencing. The fencing mask was invented in 1776, and the weight of the blade was lightened to match in the 19th century. At the first Olympic Games in Athens in 1896. In this time, male`s fencing became an official sport, and female`s fencing entered the Olympic Games in Paris in 1924 later. At present, researches on fencing mainly focus on the training, strategic, tactics and physiological mechanism. In other words, they concern the performance of fencers in training, but ignore their recovery and life. They are in an asymmetrical position for a long time in training, which is easier to accumulate fatigue in the dominant side, especially the knee joint. Pain from the overuse injury or other factors are known to affect sleep quality, but very little researches have been done for fencers. When people do not acquire good sleep, they usually feel tired easily, and have hard time to concentrate on the study and work. Athletes need to undergo greater body load than common people. The sleep disturbance due to pain may slow the body recovery speed, and further aggravate the pain and accumulate the overuse injury. Therefore, it is necessary to assess the association between the sleep disturbance and the overuse injury. The knee joint bears the main body load in fencing, hence this research select knee joint for evaluation.